PENGARUH KOMPETENSI DAN KARAKTERISTIK PEKERJAAN TERHADAP KEPUASAN KERJA DENGAN MOTIVASI SEBAGAI MEDIASI (Studi Pada Pegawai Dinas Pendidikan Kabupaten Pati) (Jurnal Mahasiswa Pasca Sarjana, 2015)
The purpose of this study to determine the effect of competencyand job characteristic on job satisfaction mediated by the work motivationat Dinas Pendidikan Kabupaten Pati. This research was conducted with a sensus method and implemented in Dinas Pendidikan Kabupaten Pati. Technical test data used in this study include validitas test, reliability test, multiple regression analysis, t test, and mediation test to verify and prove the hypothesis of the research. From the analysis and discussion show that competency does not influence on work motivation, significantly positive effect of job characteristic on work motivation, competency does not influence on job satisfaction, job characteristic significantly positive effect on job satisfaction and work motivation significantly positive effect on job satisfaction. Strong influence of copmpetency is mediated by work motivation to the job satisfaction compared directly influence toward the job satisfaction. Moreover of job characteristic has strong influence mediated by work motivation to the job satisfaction compared directly influence toward the job satisfaction. Keywords: Competency, Job Characteristic,Motivation and Job Satisfaction.